A taxonomy of digital media types for Learner-Generated Digital Media assignments. (November 2017) - Reyna, Jorge; Hanham, Jose; Meier, Peter
The notion of students as co-creators of content in higher education is gaining popularity, with an ever-increasing emphasis on the development of digital media assignments. In a separate paper, the authors introduced the Digital Media Literacies Framework, which is composed of three interrelated domains: (1) conceptual, (2) functional, and (3) audiovisual, each of which defines a set of prosumer principles used to create digital artefacts. This framework fills a gap in the literature and is the first step towards the provision of a systematic approach to designing digital media assignments. This paper expands on the Digital Media Literacies Framework through the incorporation of Technological Proxies and proposes a taxonomy of digital media types to help educators and students to visualise the skills needed to complete Learner-Generated Digital Media assignments. A taxonomy of digital media types is presented considering the conceptual, functional, and audiovisual domains of the Digital Media Literacies Framework. The taxonomy spans a range of Learner-Generated Digital Media assignments, from the creation of an audio podcast to the complexity of blended media or game development. Implications of the taxonomy for teaching and learning in higher education are discussed.